Kekosongan Regulasi dan Ketimpangan Fiskal Daerah di Sektor Kelautan: Kajian Normatif Atas Undang-Undang Cipta Kerja - Fahrur Rozi; Syofiarti Syofiarti; Dian Bakti Setiawan (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation (hereinafter the Job Creation Law) has fundamentally transformed business licensing governance in the marine sector. Through the Omnibus Law approach, this law centralizes authority that was previously decentralized to regional governments, particularly regarding marine spatial utilization licensing and regional levy collection. This study aims to examine the synchronization and harmonization of legal norms in the hierarchy of legislation after the enactment of the Job Creation Law in the marine sector, and to identify its legal implications for fiscal decentralization and Regional Original Revenue (PAD). This research employs a normative legal research method with a statutory approach. The findings indicate that the Job Creation Law creates a contradiction in terminis between norms granting authority in formal laws and norms limiting their implementation in implementing regulations, resulting in regulatory gaps at the regional level. Fiscal centralization through Government Regulation Number 85 of 2021 implies the loss of regional government potential revenue from the marine sector, estimated at IDR 205 billion from a single instrument alone, and worsens fiscal capacity disparities between regions. The regulatory framework needs refinement through proportional delegation of authority to regional governments, combined with administrative discretion under strict oversight and the formulation of local initiative regulations to address existing legal gaps.